Accuracy of FENO for diagnosing asthma: a systematic review. Issue 2 (7th July 2016) - Karrasch, Stefan; Linde, Klaus; Rücker, Gerta; Sommer, Harriet; Karsch-Völk, Marlies; Kleijnen, Jos; Jörres, Rudolf A; Schneider, Antonius
Abstract : Background: Measurement of FENO might substitute bronchial provocation for diagnosing asthma. We aimed to investigate the diagnostic accuracy of FENO measurement compared with established reference standard. Methods: Systematic review and diagnostic meta-analysis. Data sources were Medline, Embase and Scopus up to 29 November 2015. Sensitivity and specificity were estimated using a bivariate model. Additionally, summary receiver-operating characteristic curves were estimated. Results: 26 studies with 4518 participants (median 113) were included. Risk of bias was considered low for six of seven items in five studies and for five items in seven studies. The overall sensitivity in the meta-analysis was 0.65 (95% CI 0.58 to 0.72), the overall specificity 0.82 (0.76 to 0.86), the diagnostic OR 9.23 (6.55 to 13.01) and the area under the curve 0.80 (0.77 to 0.85). In meta-regression analyses, higher cut-off values were associated with increasing specificity (OR 1.46 per 10 ppb increase in cut-off) while there was no association with sensitivity. Sensitivities varied significantly within the different FENO devices, but not specificities. Neither prevalence, age, use of bronchoprovocation in >90% of participants or as exclusive reference standard test, nor risk of bias were significantly associated with diagnostic accuracy. Conclusions: There appears to be a fair accuracy of FENO for making the diagnosis of asthma. The overall specificity was higher than sensitivity, which indicates a higher diagnostic potential for ruling in than for ruling out the diagnosis of asthma.